Pengaruh Saluran Distribusi Terhadap Volume Penjualan Semen pada PT.Semen Tonasa ( Persero ) Pemasaran Wilayah II di Samarinda - Sattar Sattar (Prodi Ilmu Administrasi Negara, 2016)
The aim of this research is to know how far is thw influence of channelof distribution applied by PT. Semen Tonasa in Samarinda marketingbureau towards the producer, agents, retail and consument. The onewhich inluences them is the quantity of the distribution cannels used bythe company to market the production. In the analysis by using simpleliniar regression got the : Y = - 948.943,712 + 75.155,228 X, it meansthat every addition of the distribution channel it is hoped the volume ofthe sale will cover the substraction = 873.789,484 ton. Then to knowhow the closed relation between distribution cannels used and the effectof the sale volume (r) the result is 0,896. So r is the same or smallerthan 1, it means that those are correlated. All are determined by thequantity of the them.The other proofs are being counted by the volumeof both factors.